Βάσεις δεδομένων επιχειρήσεων στην Ελλάδα για την έρευνα σχετικά με την επιχειρηματικότητα: προβλήματα και προοπτικές - Οικονόμου, Κωνσταντίνος Χ. (SPOUDAI Journal of Economics and Business, 2006)
The author of this article aims to engage the attention of the contemporary scientific community of Greek economists, regardless of sector, concerning issues and problems with the organisation and the use of the Greek business databases. A brief theoretical discussion of the relevant literature on entrepreneurship is presented and a series of issues related to the secondary business databases and ways of their classification. The article focuses on the two main available Greek business databases, their advantages and limitations. Emphasis is placed on the V.A.T. database of the National Statistical Services of Greece. An institutionalised collaboration of the scientific community with the N.S.S.G is suggested. Attention should be paid to the improvement of existent and future business databases. The foundation of a national-level register of enterprises is proposed for firm registration and collection of relevant material. JEL Classification: M-13